Software defined internet of things in smart city: A review - Imran Edzereiq, Kamarudin; Mohamed Ariff, Ameedeen; Mohd Faizal, Ab Razak; Azlee, Zabidi (Institute of Advanced Engineering and Science, 2023)
The concept of smart cities has gained traction to enhance citizens’ quality of life amidst rapid urbanization. Integration of the Internet of Things (IoT) is a key component that allows for gathering real-time data to inform decision-making and drive innovation in urban planning and management. However, managing the amount of data generated and the IoT devices rapid growth poses a challenge that leads to network management, interoperability, security, and scalability issues in smart cities. To overcome such problems, integrating Software Define Networking (SDN) in IoT provides a flexible, scalable, and efficient network architecture that can better support the unique demands of IoT devices and applications. Motivated by the extensive research efforts in the Software Defined Internet of Things (SDIoT), this paper aims to review SDIoT implementation in smart cities. It first introduces the underlying technology along with various practical applications of SDIoT. The comprehension of SDIoT in smart cities focus on IoT application requirements, including interoperability, scalability, low latency requirement, handling of big data, security, and privacy, energy consumption, Quality of Service (QoS), and task offloading. The paper concludes by discussing the future research directions that need to be examined in greater depth.